ANTIBACTERIAL ACTIVITY AND PHYTOCHEMICAL STUDY OF ETHANOLIC EXTRACT OF TRIUMFETTA RHOMBOIDEA JACQ (International Journal of Pharmaceutical Sciences and Drug Research, 2010)
Ethanolic extract of Triumfetta rhomboidea Jacq was subjected to various phytochemical tests. Preparative Thin layer Chromatography study of the extract was performed and active constituents were isolated. Spectral analysis of the isolated constituent indicates that Triumfetta rhomboidea (Tiliaceae) contains carbohydrate glycosides, phytosterol, steroids, flavonoids, tannin & phenolic compounds and triterpenoids. Antibacterial activity of ether and alcoholic extract of the plant was performed. Results exhibited that Triumfetta rhomboidea Jacq contain good antibacterial action.